The HIV Care Cascade and sub-analysis of those linked to but not retained in care: the experience from a tertiary HIV referral service in Dublin Ireland. Issue 3 (4th May 2017) - McGettrick, P.; Ghavami-Kia, B.; Tinago, W.; Macken, A.; O'Halloran, J.; Lambert, J.S.; Sheehan, G.; Mallon, P.W.G.
Abstract : Background: The HIV Care Cascade model can be used to measure how clinical services align with United Nations' (UN) HIV treatment targets. Previous models have highlighted sequential losses at each step of the Cascade with a significant proportion being not retained in care (NRIC). Objective: We aimed to assess the feasibility of meeting the UN targets and assess factors associated with, and calculate the true proportion of those, NRIC. Methods: All people living with HIV who were linked to our service, one of three specialist HIV care providers in Dublin Ireland, from its establishment in 1993 to 1 December 2014, were included in the cohort and were categorized as linked to care, retained in care (RIC), on antiretroviral therapy (on ART), virally suppressed (HIV RNA <40copies/ml), and NRIC. An analysis of those NRIC was performed to categorize their current status through direct/indirect contact. Results: Of 1000 patients linked to care, 78.7% ( n = 787) were RIC, of whom 91.5% ( n = 720) were on ART, with 89.9% ( n = 644) virally suppressed. Those RIC were more likely older ( p = 0.006) and non-IVDU ( p < 0.001). Of 213 (21.3%) NRIC, 56 (26.3%) emigrated, 27 (12.7%) transferred care, 15 (7.0%) stopped attending but were contactable, 38 (17.8%) died, and 77 (36.1%) were lost to follow-up. After revision, 10.5% of the cohort was confirmed as NRIC, with 6 of 15 defined as "stopped attending" re-linked to care following direct contact. Conclusions: Our HIV Care Cascade model demonstrates that the true numbers of patients NRIC may be significantly lower than previously estimated and once RIC, treatment goals approaching the United Nations Programme on HIV and AIDS targets are possible with 91.5% on treatment and almost 90% of those on treatment virally suppressed. That 40% reengaged following direct contact suggests benefit through regular monitoring and direct contact based on the HIV Care Cascade model.